2017
DOI: 10.22146/jtbb.22258
|View full text |Cite
|
Sign up to set email alerts
|

Root Anatomy and Growth of Capsicum frutescens L. on Verticulture with Different Watering Supply

Abstract: The rapid increase in human population reduces land productivity in urban areas. Verticulture is a way of planting in a vertical arrangement, such as for Capsicum frutescens L. This study aimed to examine the root anatomy and growth responses of C. frutescens L. due to different watering supply on verticulture technique. Fourteen days old seedlings were grown in polybags on the ground and into vertical pots made of paralon pipe. Watering supply was given for every day, once in 3 days, and once in 6 days for 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Purushothaman et al (2012) revealed that the area of plant vascular tissue will decrease along with the lower soil moisture due to drought stress. Ratmadanti and Maryani (2017) also discovered that the diameter of stele is related to the ability of plants to uptake water and nutrients carried over the leaves that plants need for their metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Purushothaman et al (2012) revealed that the area of plant vascular tissue will decrease along with the lower soil moisture due to drought stress. Ratmadanti and Maryani (2017) also discovered that the diameter of stele is related to the ability of plants to uptake water and nutrients carried over the leaves that plants need for their metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…According to [20], biochar is able to increase water holding capacity and provide nutrients in improving nutrient uptake by plants thus increasing soil fertility. [21] states that optimal plant growth can be achieved if plants are watersufficient.…”
Section: Plant Fresh Weight (G)mentioning
confidence: 99%